“Determinación de parámetros tecnológicos de secado de almejas de agua dulce (Anodontites trapesialis). Y su evaluación fisicoquimica - Sánchez Noriega, Rene (2007)
The fresh water Clam (Anodontites trapesialis), is a typical species of the forest, reproducing in form accelerated in all the lagoons or mirrors of water dedicated to the culture and investigation of other species, introducing itself in the form of larva soon to follow its development until arriving at its state of adult. The development is uncontrollable, reasOn why the unique form to control the presence of these clams is realising its advantage by means of industrialization, which will allow to generate added value, to create new power supplies and sources of work. In this project of lnvestigation one looked for to determine technological parameters as far as the selection of the clams considering parameters like: weight, charts, you enter other characteristics of such form to obtain majors pulp yields or meat with respect to the gross weight, also determinad the most suitable parameters of processing like: ,-prebaking, salmorización and drying of fresh water clams (Anodontites trapesialis), of such form to be able to recommend the suitable methodology of processing more, to the settler who will use this species like nutritional source. In the operation of prebaking three in order to determine the time and temperatura but suitable tests were realised; also different times and brine concentrations practicad, in which the pulp of the totally clean clam was introduced, of such form to obtain the best flavor and the recommended optima! pH for other species similar to the studied one; and the most important operation was the drying, for which three different methods practicad: Drying in stove, convective solar drying (prototype of dryer solar) and dried lot of direct exposure (barbecues); for which one was to maintain approximate a constant temperatura of 60ºC and to consider the times based on the used method, soon the dry samples were packagin in polythene films and they were put under a storage to room temperatura (Tº= 26±2 ºC) for its later chemical and microbiological physical analysis. In order to determine the best treatment of the tests realised as much for the prebaking as of salmorización the test of preference was used, for which it was had a semi trained panel. The flow of recommended processing, to obtain salty Clams dry is: Reception of the raw material, first washing, desvalvado and eviscerated, secondly washed, prebaking (80ºC by 7 minutes), cooled, salmorizado (10 minutes in solution to 10% of salt and 0.6% of citric acid), oreado (time of 20 minutes), dried: Drying in stove; time of 2 hours 50 minutes to temperature of 60ºC, storage to temperature of 26±2ºC. Also the proximal chemical composition of the part food of the fresh water clam as end ítem were; Humidity: 58.53%, protein: 28. 79%, fat: 4.45%, ash: 2.50% and others: 5. 73%. • The yield average in pulp is acceptable with respect to other bivalve sailors, having to handle itself and to spread concerning the coastal population and people dedicated to the piscicultura! activity, its kindness and consumptions of this species.